Regulation by Nrf2 of IL-1β-induced inflammatory and oxidative response in VSMC and its relationship with TLR4 - González-Carnicero, Zoe; Hernanz, Raquel; Martínez-Casales, Marta; Barrús, María Teresa; Martín, Ángela; Alonso, María Jesús (Frontiers in Pharmacology, 2023)
Vascular oxidative stress and inflammation play an important role in the pathogenesis of cardiovascular diseases (CVDs). The proinflammatory cytokine Interleukin-1β (IL-1β) participates in the vascular inflammatory and oxidative responses and influences vascular smooth muscle cells (VSMC) phenotype and function, as well as vascular remodelling in CVDs. The Toll-like receptor 4 (TLR4) is also involved in the inflammatory response in CVDs. A relationship between IL-1β and TLR4 pathway has been described, although the exact mechanism of this interaction remains still unknown. Moreover, the oxidative stress sensitive transcription factor nuclear factor-erythroid 2-related factor 2 (Nrf2) promotes the transcription of several antioxidant and anti-inflammatory genes. Nrf2 activators have shown to possess beneficial effects in CVDs in which oxidative stress and inflammation are involved, such as hypertension and atherosclerosis; however, the molecular mechanisms are not fully understood. Here, we analysed the role of TLR4 in the oxidative and inflammatory effects of IL-1β as well as whether Nrf2 activation contributes to vascular alterations by modulating these effects. For this purpose, VSMC and mice aortic segments stimulated with IL-1β were used. IL-1β induces MyD88 expression while the TLR4 inhibitor CLI-095 reduces the IL-1β-elicited COX-2 protein expression, reactive oxygen species (ROS) production, VSMC migration and endothelial dysfunction. Additionally, IL-1β increases Nrf2 nuclear translocation and expression of its downstream proteins heme oxygenase-1, NAD(P)H:quinone oxidoreductase 1 and superoxide dismutase-2, by an oxidative stress-dependent mechanism; moreover, IL-1β reduces the expression of the Nrf2 inhibitor Keap1. The Nrf2 activator tert-butylhydroquinone (tBHQ) reduces the effects of IL-1β on the increased ROS production and the expression of the proinflammatory markers (p-p38, p-JNK, p-c-Jun, COX-2), the increased cell proliferation and migration and prevents the IL-1β-induced endothelial dysfunction in mice aortas. Additionally, tBHQ also reduces the increased MyD88 expression, NADPHoxidase activity and cell migration induced by lipopolysaccharide. In summary, this study reveals that TLR4 pathway contributes to the prooxidant and proinflammatory IL-1β-induced effects. Moreover, activation of Nrf2 prevents the deleterious effects of IL-1β, likely by reducing TLR4 -dependent pathway. Although further research is needed, the results are promising as they suggest that Nrf2 activators might protect against the oxidative stress and inflammation characteristic of CVDs.